Measuring the effectiveness of psychologically oriented basketball drills in team practice to improve self-regulation - Altfeld, S.; Langenkamp, H.; Beckmann, J.; Kellmann, M. (International Journal of Sports Science & Coaching, 2017)
It has repeatedly been shown that effective regulation of one's emotional states is crucial for high performance in sports. However, self-regulation skills need to be learned and practiced by players for effective use. The present study examined the effectiveness of newly designed basketball drills for regular team practice for implementing and improving self-regulation skills in young basketball players. A quasi-experimental design with four measurements and two follow-ups was applied. The sample included two teams (N?=?20) of the highest national under 16 youth basketball league of Germany. The intervention group was instructed in self-regulation skills (e.g. self-talk, self-relaxation, routines) at the beginning of the intervention. Subsequently, the techniques were practiced in the course of eight psychologically oriented basketball drills between the second and fourth measurement. The sport-specific Volitional Components Questionnaire and the Action Control Scale Sport were used in this study. Results indicated that the intervention group improved significantly in the factors measuring self-motivation and dealing with negative thoughts while the control group showed no significant effects. The effects were maintained in the follow-ups. The results imply that learned and practiced strategies to regulate one's emotional state have long-term benefits for players.